Research on learning objects quality and reusability - Ignaško, Elvyra; Kurilovas, Eugenijus (Lietuvos matematikos rinkinys, 2010)
The paper is aimed to analyse the learning objects quality evaluation model taking into account learning objects reusability principles. Multiple criteria analysis methods and quality evaluation criteria identification principles are used to create the learning objects quality evaluation model. The portrait of the sets of the learning objects reusability principles and the learning objects quality evaluation criteria is presented in the paper. This portrait shows the bilateral cohesion of these principles and criteria. The presented learning objects quality evaluation model is usable in education institutions while selecting learning objects in the market or free-of-charge repositories.